Penerapan Model Pembelajaran STAD Untuk Meningkatkan Hasil Belajar Siswa - Erni Widhiastuti (Universitas Sebelas Maret, 2020)
To improve student learning outcomes in the learning process, one of them is by applying the STAD learning model. STAD learning model is a cooperative learning model that emphasizes student activities and interactions in the form of groups. By applying the STAD learning model, it can improve student learning outcomes that are low with the motivation and help of friends in the group. STAD is a cooperative learning model that encourages student collaboration through learning in groups whose members are diverse both in academic ability and background in order to create mutual encouragement and help each other in a diverse social atmosphere to master the skills being studied.